Experimental and FEM Analyses of RC Beams with Radius Corner Arch at Bottom Tension Face - Maryam H. Naser; Fatimah H. Naser; Ali Hameed Naser Almamoori; Mohammed L. Hussien (Journal of Rehabilitation in Civil Engineering)
The present study includes experimental and numerical investigations of the behavior and the load carrying capacity of RC two-hinged beams with radius corner arch at the bottom face subjected to static loading conditions. The experimental program included four specimens with the same volume of concrete and amount of steel reinforcement but, with a different span of the arch (1180 mm, 900 mm, 740 mm, and 600 mm). The goals were to evaluate the effect of a span of the arch and to find the optimum ratio of the arch length to beam span for the maximum load capacity as well as to validate the numerical results taken from the finite element model. From the results of this work, it was found that the best load carrying capacity for the beam with a radius corner arch is when the arch length/beam span ratio is equal (0.62). Also, the FEM result seems efficient and gives good accuracy through comparison with the experimental results.